2012
DOI: 10.1136/bmj.e4693
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of psychosocial intervention in patients with mild Alzheimer's disease: the multicentre, rater blinded, randomised Danish Alzheimer Intervention Study (DAISY)

Abstract: Objective To assess the efficacy at 12 months of an early psychosocial counselling and support programme for outpatients with mild Alzheimer's disease and their primary care givers.Design Multicentre, randomised, controlled, rater blinded trial. Setting Primary care and memory clinics in five Danish districts.Participants 330 outpatients with mild Alzheimer's disease and their 330 primary care givers.Interventions Participating dyads (patient and primary care giver) were randomised to control support during fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 43 publications
2
91
0
1
Order By: Relevance
“…However, many studies fail to report positive outcomes (Olazaran et al, 2010). For example, recent pragmatic trials of support programmes (Kurz et al, 2012;Low et al, 2013;Van de Ven et al, 2013;Waldorff et al, 2012), telecare (Bardsley, Steventon, & Doll, 2013), training interventions (Beer et al, 2011;Spijker et al, 2011) and system enhancements or novel methods of delivering services (Goldberg et al, 2013;Meeuwsen et al, 2012;Nourhashemi et al, 2010;Van Houdt & De Lepeleire, 2010) all report no positive effects compared with the control 'usual care' condition. One study nonetheless demonstrated improvements in the patient experience and family carer satisfaction (Goldberg et al, 2013) whilst others point to problems with delivery of the intervention by practitioners such as poor adherence and variation in practice (Low et al, 2013;Spijker et al, 2013;Wenborn et al, 2013).…”
Section: Success and Failure Of Psychosocial Interventionsmentioning
confidence: 99%
“…However, many studies fail to report positive outcomes (Olazaran et al, 2010). For example, recent pragmatic trials of support programmes (Kurz et al, 2012;Low et al, 2013;Van de Ven et al, 2013;Waldorff et al, 2012), telecare (Bardsley, Steventon, & Doll, 2013), training interventions (Beer et al, 2011;Spijker et al, 2011) and system enhancements or novel methods of delivering services (Goldberg et al, 2013;Meeuwsen et al, 2012;Nourhashemi et al, 2010;Van Houdt & De Lepeleire, 2010) all report no positive effects compared with the control 'usual care' condition. One study nonetheless demonstrated improvements in the patient experience and family carer satisfaction (Goldberg et al, 2013) whilst others point to problems with delivery of the intervention by practitioners such as poor adherence and variation in practice (Low et al, 2013;Spijker et al, 2013;Wenborn et al, 2013).…”
Section: Success and Failure Of Psychosocial Interventionsmentioning
confidence: 99%
“…In the present case, a 1-year follow-up on the effect of the intervention reported no overall difference between groups [10]. However, in a qualitative study, patients and caregivers indicated that they found the intervention stimulating and rewarding and that it helped them to find new ways to cope with the challenges of the disease [33].…”
Section: Discussionmentioning
confidence: 99%
“…The fields of geriatrics, psychiatry, neurology, psychology, care science, family medicine, and law were involved in the development of a psychosocial supportive intervention to be tested in a randomised controlled trial [9]. Clinical evaluation after 1 year of follow-up demonstrated no effect on most of the applied outcome measures [10]. However, further analysis in a social decision-making context is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…15 Recent RCTs of psychosocial interventions in Europe (UK, Denmark and Norway) using different models have been ineffective in terms of carer psychological symptoms and QoL, thus showing that our findings were not explained solely by the offer of a therapist to spend time and attention. 24,61,62 The earliest study of the three used trained ex-carers in a voluntary sector befriending intervention and was not taken up by many carers. 24 This suggests that acceptability, as well as the theoretical background, needs to be a major focus of any intervention.…”
Section: Overall Evidencementioning
confidence: 99%
“…Danish Alzheimer's Intervention Study (DAISY) was a multifaceted intervention involving both the person with mild Alzheimer's disease and the carer. 61 The intervention was individualised to the dyad, who were seen both individually and together by a nurse for counselling, based on validating the participants and focusing on retained and positive attributes and skills. It allowed patient and carer to tell their own life story and explain what mattered to them.…”
Section: Overall Evidencementioning
confidence: 99%